Neurotrophic basis to the pathogenesis of depression and phytotherapy - Wang, Huiqin; Yang, Yantao; Pei, Gang; Wang, Zhenzhen; Chen, Naihong (Frontiers in Pharmacology, 2023)
Depression is a major neuropsychiatric disease that considerably impacts individuals’ psychosocial function and life quality. Neurotrophic factors are now connected to the pathogenesis of depression, while the definitive neurotrophic basis remains elusive. Besides, phytotherapy is alternative to conventional antidepressants that may minimize undesirable adverse reactions. Thus, further research into the interaction between neurotrophic factors and depression and phytochemicals that repair neurotrophic factors deficit is highly required. This review highlighted the implication of neurotrophic factors in depression, with a focus on the brain-derived neurotrophic factor (BDNF), glial cell line-derived neurotrophic factor (GDNF), vascular endothelial growth factor (VEGF), and nerve growth factor (NGF), and detailed the antidepressant activities of various phytochemicals targeting neurotrophic factors. Additionally, we presented future opportunities for novel diagnostic and therapeutic strategies for depression and provided solutions to challenges in this area to accelerate the clinical translation of neurotrophic factors for the treatment of depression.